Comprehensive single-cell analysis reveals novel anergic antigen-presenting cell subtypes in human sepsis - Zhang, Tuo; Lian, Guodong; Fang, Wei; Tian, Lei; Ma, Wenhao; Zhang, Jicheng; Meng, Zhaoli; Yang, Hongna; Wang, Chunting; Wei, Chengguo; Chen, Man (Frontiers in Immunology, 2023)
Background: Sepsis is a life-threatening condition with high mortality. A few studies have emerged utilizing single-cell RNA sequencing (scRNA-seq) to analyze gene expression at the single-cell resolution in sepsis, but a comprehensive high-resolution analysis of blood antigen-presenting cells has not been conducted.All published human scRNA-seq data were downloaded from the single cell portal database. After manually curating the dataset, we extracted all antigen-presenting cells, including dendritic cells (DCs) and monocytes, for identification of cell subpopulations and their gene profiling and intercellular interactions between septic patients and healthy controls. Finally, we further validated the findings by performing deconvolution analysis on bulk RNA sequencing (RNA-seq) data and flow cytometry.Results: Within the traditional DC populations, we discovered novel anergic DC subtypes characterized by low major histocompatibility complex class II expression.Notably, these anergic DC subtypes showed a significant increase in septic patients.Additionally, we found that a previously reported immunosuppressive monocyte 3 subtype, Mono1, exhibited a similar gene expression profile to these anergic DCs. The consistency of our findings was confirmed through validation using bulk RNA-seq and flow cytometry, ensuring accurate identification of cell subtypes and gene expression patterns.This study represents the first comprehensive single-cell analysis of antigen-presenting cells in human sepsis, revealing novel disease-associated anergic DC subtypes. These findings provide new insights into the cellular mechanisms of immune dysregulation in bacterial sepsis.